2022
DOI: 10.1111/hsc.13870
|View full text |Cite
|
Sign up to set email alerts
|

‘I feel like my house was taken away from me’ : Parents' experiences of having home adaptations for their medically complex, technology‐dependent child

Abstract: Children who are dependent upon technology are resource-intensive (Breneol et al., 2019), a high-cost subpopulation of seriously ill babies, children and young people with life-limiting conditions (de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…22 Therefore, we should support home care to improve parents' and their children's physical, emotional, and mental health. 23 Our participants reported that they struggled with the increased burden of care after their children were discharged. They added that they were socially isolated because they could not share their burden with other family members and feared that they would not be accepted by society.…”
Section: Discussionmentioning
confidence: 94%
“…22 Therefore, we should support home care to improve parents' and their children's physical, emotional, and mental health. 23 Our participants reported that they struggled with the increased burden of care after their children were discharged. They added that they were socially isolated because they could not share their burden with other family members and feared that they would not be accepted by society.…”
Section: Discussionmentioning
confidence: 94%
“…Children with SMID require 24-h caregiving, thus, creating a physical and psychological burden for primary caregivers who are mostly mothers. They face physical and emotional strain from daily caregiving (4)(5)(6), limited opportunities to do their work or participate in social activities (7,8), and restrictions on family time (9).…”
Section: Introductionmentioning
confidence: 99%